Various Factors Related to The Quality of Living Pulmonary Tuberculosis Patients - Sukartini, GaTintin; Rahman, Gazali; Suarilah, Ira (International Journal of Psychosocial Rehabilitation, 2020)
A low quality of life has still experienced by many pulmonary tuberculosis (TB) sufferers. The quality of life of patients with pulmonary TB is influenced by many factors that differ for each patient depending on economic and socio-cultural conditions in the area. This study was purposed to find out what factors were associated with the quality of life for people with pulmonary TB by using the Health Promotion Model from Pender. A cross-sectional design was used in this study. The sample size was 20 respondents. Independent variables include gender, age, BMI; education, occupation, marital status, total income; anxiety and depression; assessment of the benefits of action; assessment of barriers to action; behavior which is in accordance with health promotion. While the dependent variable was quality of life. The instruments used include demographic data, K10, barrier modification questionnaire, benefit modification questionnaire, and lifestyle profile modification questionnaire, and SF-36v2. The analysis used a Spearman rank with a significance level of α = 0.05. The results showed that many pulmonary TB sufferers had a low quality of life, mainly from the physical domain (17 people) and mental domain (14 people). Only the age variable (p = 0.027) was related to the quality of life of patients with pulmonary TB from the mental domain. However, these factors were not related to the quality of life of patients with pulmonary TB. The theory of HPM has many factors, other researchers can use other factors from HPM to determine the quality of life for people with pulmonary TB. Primary healthcare can improve health promotion patterns in the program to eradicate and prevent pulmonary TB.